A comparison of cerebral atrophy in CT scan findings among alcoholic groups - Ishii, T (Acta psychiatrica Scandinavica. Supplementum, 1983)
Seventy-five alcoholic patients and 94 control subjects were examined by CT scans and measured by 11 measurement items on CT. The alcoholics were classified and compared. Enlargement of ventricles was recognized in the alcoholics. The degree of enlargement of ventricles was extremely striking in alcoholic dementia. The increasing tendencies toward cerebral atrophy in a given age stratum were almost parallel in the controls and the alcoholics, with a difference in the degree of atrophy. It was suggested that the enlargement of the ventricular system in the alcoholics might be induced in the initial stage of alcohol dependence, and that physiological atrophy due to aging might progress thereafter. The results of multivariate canonical analysis of these CT items suggested that the CT indicators effective for evaluating alcoholic cerebral atrophy were the transverse diameter of the third ventricle, Ventricle index and Evans' index.